Gut microbiota in women with gestational diabetes mellitus has potential impact on metabolism in pregnant mice and their offspring - Qin, Shengtang; Wang, Yutong; Wang, Shuxian; Ning, Bohan; Huai, Jing; Yang, Huixia (Frontiers in Microbiology, 2022)
Studies have shown that gestational diabetes mellitus (GDM) is closely related to abnormalities in the gut microbiota, and the offspring of these women have an increased risk of diabetes. There is no direct evidence of whether bacteria in women with GDM colonize the intestinal tract of offspring and cause hyperglycemia. In this fecal microbiota transplantation (FMT), pregnant mouse model study, two groups of germ-free (GF) mice after FMT showed different colonization patterns of gut microbiota and phenotype. Compared with the control group (healthy-FMT), we found in the GDM-FMT group as a lower relative abundance of Akkermansia and Faecalibacterium; a lower content of short-chain fatty acids and naringenin in feces; an elevated blood glucose; an inflammatory factor expression (TNF-α, CXCL-15, and IL-6), and a hepatic fat deposition. In addition, the influence of the gut microbiota continued in offspring. The gut microbiota of the offspring of GDM-FMT mice was still different from that of the control group as a lower relative abundance of Akkermansia and Parvibacter; and a higher relative abundance of bacteria such as Oscillibacter, Romboutsia, and Harryflintia. In addition, the offspring of GDM-FMT mice had higher body weight and blood glucose levels than the control offspring.